CFN lectures on functional nanostructures. Volume 2 nanoelectronics - Röthig, Christian; Schön, Gerd.; Vojta, Matthias; SpringerLink (Online service). (Berlin New York Springer, 2011)
This series of books contains selected and edited lectures from summer schools organized by the Center for Functional nanostructures (CFN) at the University of Karlsruhe. The mission of the CFN is to carry out research in the following areas: nanophotonics, nanoelectronics, molecular nanostructures and nanostructured materials. The aim of the summer schools is mainly to exchange new ideas and illustrate emerging research methodologies through a series of topical, introductory lectures. This is reflected by both the selection of topics addressed in the present volume, nanoelectronics, as well as the tutorial aspect of the contributions.
Simulating Strongly Correlated Quantum Systems: Adaptive Time-Dependent Density-Matrix Renormalization Group -- Molecular Conductance From Ab Initio Calculations: Self Energies and Absorbing Boundary Conditions -- Recent Advances in Studies of Current Noise -- Josephson Qubits as Probes of 1/f Noise -- Scanning Tunneling Spectroscopy -- Manipulating Single Spins in Quantum Dots Coupled to Ferromagnetic Leads -- Adiabatic Spin Pumping With Quantum Dots -- Spin Relaxation: From 2D to 1D -- Electronic Transport Properties of Superconductor-Ferromagnet Hybrid Structures.
Electronic reproduction.
Keywords: Nanoelectronics; Electronic books